Pengaruh Latihan Passing Bawah Menggunakan Target Dinding Dalam Kemampuan Passing Bawah Pada Siswa Ekstrakurikuler Bola Voli SMPIT Nurul Ihsan - Muhammad Reza Syahputra, Reza; Setiawan, Asep; Lasma, Yunita (Motion: Journal Research of Physical Education, 2024)
This research aims to determine the effect of down passing training using a wall target on the down passing ability of volleyball extracurricular students at SMPIT Nurul Ihsan. The research method used was an experiment with a One-Group Pretest-Posttest design. The research subjects were 15 students who actively participated in volleyball extracurriculars at SMPIT Nurul Ihsan. The data collection instrument uses the AAHPER test to measure bottom passing ability before and after practice. The results of the study showed a significant increase in down passing ability after being given training using a wall target. Hypothesis testing using the t-test shows a calculated t value of 8.33 with a t table of 1.761, so it can be concluded that down passing training using a wall target is effective in improving students' down passing ability. This research provides an important contribution for volleyball coaches in designing more effective training programs to improve players' basic skills.